Colonic delivery of compression coated nisin tablets using pectin/HPMC polymer mixture - GÜRBÜZ, BURÇAK; UĞURLU, TİMUÇİN; SOYOĞUL GÜRER, ÜMRAN (ELSEVIER, 2007)
Nisin containing pectin/HPMC compression coated tablets were prepared and their in vitro behavior tested for colonic delivery. Nisin is a 34-amino-acid residue long, heat stable peptide belonging to the group A lantibiotics with wide antimicrobial activity against Grampositive bacteria. The invention can be useful for treating colonic infectious diseases such as by Clostridium difficile, and also by colonization of vancomycin-resistant enterococci. In this study, each 100 mg core tablet of nisin was compression coated with 100% pectin, 90% pectin-10% HPMC, 85% pectin-15% HPMC, 80% pectin-20% HPMC 75% pectin-25% HPMC, 100% HPMC at a coat weight of 400 mg. The concentration and the activity of nisin were quantified using Well Diffusion Agar Assay. Drug release studies were carried out in pH 3.3 buffer solution. System degradation/erosion experiments were carried out in pH 1.2, 3.3, and 6.8 buffers using a pectinolytic enzyme. The biological activity and NMR studies were performed to assess the stability of nisin during the processing and after the in vitro tests. It was found that pectin alone was not sufficient to protect the nisin containing core tablets. At the end of the 6 h 40% degradation was observed for 100% pectin tablets. HPMC addition required to control the solubility of pectin, a 5% increase in HPMC ratio in pectin/HPMC mixture provided a 2-h lag time for nisin release. Eighty percent pectin-20% HPMC appeared to be an optimum combination for further evaluation. Tablets maintained their integrity during the 6-h dissolution test, approximating the colon arrival times. Nisin was found to be active/stable during processing and after in vitro tests. Effect of polymer hydration on pectin degradation was found to be crucial for the enzyme activity. Sufficiently hydrated pectin degraded faster. The pectin/HPMC envelope was found to be a good delivery system for nisin to be delivered to the colon. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: colonic delivery; nisin; pectin; HPMC; compression coating; NMR; well diffusion agar assay; DRUG-DELIVERY; POLYSACCHARIDES; LANTIBIOTICS